Cathodes for Zinc-Ion Micro-Batteries: Challenges, Strategies, and Perspectives - Ling Deng; Qunfang Lin; Zeyang Li; Juexian Cao; Kailing Sun; Tongye Wei (Batteries)
The sustainable development of high-performance micro-batteries, characterized by miniaturized size, portability, enhanced safety, and cost-effectiveness, is crucial for the advancement of wearable and smart electronics. Zinc-ion micro-batteries (ZIMBs) have attracted widespread attention for their high energy density, environmental friendliness, excellent safety, and low cost. The key to designing high-performance ZIMBs lies in improving their volumetric capacity and cycle stability. This review focuses on material design, electrode fabrication, and the structural configuration of micro-batteries, providing a comprehensive analysis of the challenges and strategies associated with cathodes in ZIMBs. Additionally, the application of ZIMBs, which provide energy for electronics such as wearable devices, tiny robots, and sensors, is introduced. Finally, future perspectives on cathodes for ZIMBs are discussed, offering key insights into their design and fabrication in order to facilitate the successful integration of ZIMBs into practical applications.